Consumers’ Awareness on Organic Food: Case of Urban Sri Lanka - Malkanthi, S.H. Pushpa; Rathnachandra, S.D. Dilini; Weerasinghe, W.A. Ruwani N. (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2021)
The organic food market is rapidly expanding all over the world with the recent rise of concern in food safety and environmental protection. Thus, examining information about consumers’ awareness on organic food is one of the inspiring areas for producers and marketers to capture a greater market share successfully. Therefore, this study aimed at analyzing the consumer awareness towards organic food products while addressing socio-demographic factors affecting consumer awareness on organic food, knowledge of consumers about organic food, and their purchasing pattern. A sample of 600 consumers was selected from the main cities of six urban districts in Sri Lanka for the study. Data were collected via a consumer survey using a pre-tested questionnaire, from November 2018 to May 2019. The data analysis was carried out using frequencies, percentages, and multiple linear regression analysis. According to the results, the majority of the respondents were married females. The results revealed that Sri Lankan consumers have a better awareness on organic food. The results of the regression analysis highlighted that the consumers’ awareness is significantly affected by factors such as gender, marital status, education, and monthly income. Although most respondents have a good level of awareness on organic food, their buying trend is at a lower level. The findings of the study play an important role in promoting the organic food market and are essential for food marketing planners, researchers, and policymakers to enhance the organic food industry in the country in the future.